1992
DOI: 10.1104/pp.99.3.1021
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Partitioning in Intact Roots of Aluminum-Tolerant and Aluminum-Sensitive Wheat (Triticum aestivum L.) Cultivars

Abstract: Aluminum (Al) partitioning in intact roots of wheat (Triticum aestivum L.) cultivars that differ in sensitivity to Al was investigated. Roots of intact seedlings were exposed to Al for up to 24 hours and distribution of Al was assessed visually by hematoxylin staining or by direct measurement of concentration of Al by atomic absorption spectrophotometry or ion chromatography. Major differences in Al accumulation between Al-tolerant (Atlas 66) and Al-sensitive (Tam 105) cultivars were found in the growing reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
72
3
6

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(95 citation statements)
references
References 26 publications
14
72
3
6
Order By: Relevance
“…Previous measurements of total Al contained at the tip (after a citrate wash) had suggested such a result with soybean (Lazof et al, 1994b). Root tip Al concentrations were found to be lower in Al-tolerant genotypes with other plant species as well (Rincó n and Gonzalez, 1992;Tice et al, 1992;Delhaize et al, 1993a;Ryan et al, 1997;Samuels et al, 1997;Larsen et al, 1998). A myriad of processes could contribute to Al exclusion from the meristematic cell region, including increased secretion of mucilage (Horst et al, 1982;Crawford and Wilkens, 1997), polypeptides (Basu et al, 1999), inorganic phosphate (Pellet et al, 1996), and organic acids (Delhaize et al, 1993b;Basu et al, 1994;Delhaize and Ryan, 1995;Pellet et al, 1995;Larsen et al, 1998).…”
Section: Discussionmentioning
confidence: 74%
“…Previous measurements of total Al contained at the tip (after a citrate wash) had suggested such a result with soybean (Lazof et al, 1994b). Root tip Al concentrations were found to be lower in Al-tolerant genotypes with other plant species as well (Rincó n and Gonzalez, 1992;Tice et al, 1992;Delhaize et al, 1993a;Ryan et al, 1997;Samuels et al, 1997;Larsen et al, 1998). A myriad of processes could contribute to Al exclusion from the meristematic cell region, including increased secretion of mucilage (Horst et al, 1982;Crawford and Wilkens, 1997), polypeptides (Basu et al, 1999), inorganic phosphate (Pellet et al, 1996), and organic acids (Delhaize et al, 1993b;Basu et al, 1994;Delhaize and Ryan, 1995;Pellet et al, 1995;Larsen et al, 1998).…”
Section: Discussionmentioning
confidence: 74%
“…However, some plants have evolved Al tolerance mechanisms that enable them to grow in Al-toxic, acid soil environments (for review, see Kochian, 1995;Ma et al, 2001). Earlier work in this field showed that Al tolerance in wheat (Triticum aestivum) was associated with a reduced accumulation of Al in the root apex, but not the mature root (see, for example, Rincon and Gonzales, 1992;Tice et al, 1992; Delhaize et al, 1993a). Delhaize et al (1993aDelhaize et al ( , 1993b subsequently provided compelling evidence for the existence of an Al tolerance mechanism based on root tip Al exclusion that involved Al-activated release of malate from the root apex of an Al-tolerant near-isogenic line of wheat.…”
mentioning
confidence: 99%
“…The first important publications related to this mechanism were presented in studies on wheat from the beginning of the 1990s. Rincón & Gonzalez (1992) observed that the level of sensitivity to Al was correlated with its concentration in the meristems, suggesting that the metabolic exclusion in the meristems was an important mechanism of tolerance. Delhaize et al (1993) investigated the function of the organic acids and observed that the presence of Al in the nutrient solution stimulated the secretion of malic acid.…”
Section: Resultsmentioning
confidence: 82%